Effect of the Satir Model - Based Psychoeducational Program on Parents and Children with Autism Spectrum Disorder: Satir Based Psychoeducational Program for Parents of ASD - Srikosai, Soontaree; Dornnork, Patarawadee; Somchai, Chulaporn; Sriseub, Peungpid; Taweewattanaprecha, Siriwan; Saipanish, Ratana (International Journal of Child Development and Mental Health, 2019)
Parents who have a child with autism spectrum disorder (ASD) have constant negative emotions associated with their child's self-care, social skills deficit, and self-regulation difficulties. This study compares the clinical symptoms and medical compliance of children with ASD, and the life congruence and stress of parents who participated in a psychoeducational program based on the Satir Model (PPSM) and those in a standard educational program (SEP). A randomized controlled trial design was conducted. The experimental group of 26 parents of ASD children attended the PPSM, and the control group of 23 parents attended the SEP. Data was collected using the Vineland Adaptive Behavior Scale (VABS), Patient drug compliance questionnaires, Life Congruence Scale, and Parenting Stress Index-4-SF. The mean age of the 49 participants was 39 years old. Compared to the control group, the clinical symptoms of ASD children in the experimental group were better than the control group at week28 follow up (mean difference = 13.46, p<0.05); and the percentage of drug compliance in the experimental group was better at post-test (mean difference = 5.26, p<0.05). Parental stress scores between groups were not significantly different at each follow up interval. Experimental group stress scores were reduced at week16 (p < 0.05) and week28 follow up (p < 0.01). Control group stress scores were reduced at post-test (p<0.05). Furthermore, the experimental group reported better results on the Life Congruence Scale at week8 follow up (mean difference = 11.54, p<0.05). The Satir model-based psychoeducational program helped parents of children with ASD to be more congruent and less stressed, which consequently improved clinical symptoms and the medical compliance of their children.